1949
DOI: 10.6028/jres.042.020
|View full text |Cite
|
Sign up to set email alerts
|

Accurate determination of the deadtime and recovery characteristics of Geiger-Muller counters

Abstract: A brief description of the theory of operation of Geiger-Milller counters is presented, with special emphasis on the deadtime and recovery characteristics. An electronic gating instrument is described that has been developed for the determination of deadtime and recovery characteristics to an accuracy of 1 percent or 2 microseconds. Experimental data are presented showing variation of dead time and recovery time with counter pressure and overvoltage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1953
1953
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…During this time, the SNSPD starts being able to detect another photon, albeit with limited efficiency. The DE increases with time until the entire current flows again through the SNSPD only and the system is ready to detect another photon, exactly as it was ready to detect the first one . Following Migdal et al., the first step, at which no second photon can be detected at all, is called dead time ( t dead ), while the second step, at which the DE is gradually recovered is called reset time ( t reset ).…”
Section: Intrinsic Properties and Functionalitymentioning
confidence: 99%
“…During this time, the SNSPD starts being able to detect another photon, albeit with limited efficiency. The DE increases with time until the entire current flows again through the SNSPD only and the system is ready to detect another photon, exactly as it was ready to detect the first one . Following Migdal et al., the first step, at which no second photon can be detected at all, is called dead time ( t dead ), while the second step, at which the DE is gradually recovered is called reset time ( t reset ).…”
Section: Intrinsic Properties and Functionalitymentioning
confidence: 99%
“…The name references included here are primarily those who were indirectly or marginally associated with these activities. America) actions, 108 Ernst resolution (1932), 115 Erskine resolution (1928), 113 physics, 328 Physics Committee Report (8-52), 331 refresher courses, 327 safety recommendations (1927), [109][110][111][112] Standardization Committee, SC/RSNA, ,* 108 technical program, 328 papers submitted, 328-331 Rutherford (unit), 273,275 resolution, 275 S safety recommendation (U.S.) ARRS (1922), 4 RSNA (1927), [109][110][111] (see also, protection, reference, Taylor, 1979) scattered radiation measurement, 17 SC/RSNA (Standardization Committee, RSNA) (see also, Appendix A) approach NBS, 11 defines roentgen, 9, 60 definition of x-ray intensity, 112 electron equilibrium, 61 standard air ionization chamber, 61, 112 initial meeting (1925), 8 Lauritsen proposals, 62-63 meeting , 272-273 meeting (9-47), 273 program, 273 report, 274 meeting (12-47), 276 relations with CRUSP, 276 membership, 115 1928 An account of the initial U.S. concerns with, and subsequent efforts to cope with, the safe use of ionizing radiation is given.…”
Section: Theoretical Studiesmentioning
confidence: 99%
“…It is worth addressing that these traditional models have been applied commonly in radiation detection measurements 16 . Previous studies 6,17,18 have shown that true deadtime behavior falls somewhere between the idealized models.…”
mentioning
confidence: 98%